Analysis of Strategic Choices of Malaysian SME Software Firms - Ling, Sie Chiong (2013)
This project conducted a qualitative study of the business level strategic choices of 13 Malaysian SME Software firms which are listed on the Malaysian ACE market. The study analyzed the public information available on these firms using Hambrick and Fredrickson’s (2001) Strategy Diamond framework for business level strategy, the components of which are populated from findings collected via literature review. It was found that there was some co-relation between theory and the actual strategic choices and results of these firms. Differentiation, a focus on high price market segments and clarity on strategic arenas were key success factors, while issues in the capability to execute strategic choices surfaced for some of the strategic components.